Circulating TGF‐β1 and VEGF and risk of cancer among liver transplant recipients. (27th April 2015) - Engels, Eric A.; Jennings, Linda; Kemp, Troy J.; Chaturvedi, Anil K.; Pinto, Ligia A.; Pfeiffer, Ruth M.; Trotter, James F.; Acker, Michelle; Onaca, Nicholas; Klintmalm, Goran B.
<x xml:space="preserve">Abstract</x> In this case–control study of cancer in liver transplant recipients, we found elevated levels of TGF‐β1 and VEGF in lung cancer cases compared to controls; levels were not increased among cases with colorectal, kidney, or skin cancers. However, both TGF‐β1 and VEGF were associated with PF4 levels and platelet counts, consistent with release during platelet degranulation, and platelet levels were increased in lung cancer cases. Thus, our study does not provide support for a role of TGF‐β1 and VEGF in the etiology of cancer among transplant recipients. <boxed-text content-type="graphic" id="cam4455-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>